Antibody Targeting of Cathepsin S Inhibits Angiogenesis and Synergistically Enhances Anti-VEGF - Ward, Claire (Public Library of Science, 2010)
BACKGROUND: Angiogenesis is a key hallmark of tumourigenesis and its inhibition is a proven strategy for the development of novel anti-cancer therapeutics. An important aspect of early angiogenesis is the co-ordinated migration and invasion of endothelial cells through the hypoxic tumour tissue. Cathepsin S has been shown to play an important role in angiogenesis as has vascular endothelial growth factor (VEGF). We sought to assess the anti-angiogenic effect of Fsn0503, a novel cathepsin S inhibitory antibody, when combined with anti-VEGF on vascular development. METHODOLOGY/PRINCIPAL FINDINGS: Cathepsin S expression and secretion from endothelial cells was characterised using RT-PCR and western blotting. We further show that cathepsin S promotes pericellular hydrolysis of extracellular matrix components in the tumour microenvironment and facilitates endothelial invasion. The cathepsin S inhibitory antibody, Fsn0503, blocks extracellular proteolysis, inhibiting endothelial invasion and tube formation in cell-based assays. The anti-angiogenic effects of Fsn0503 were also shown in vivo where it significantly retarded the development of vasculature in human xenograft models. Furthermore, when Fsn0503 was combined with an anti-VEGF antibody, a synergistic inhibition of microvascular development was observed. CONCLUSIONS/SIGNIFICANCE: Taken together, this data demonstrates that the antibody-mediated targeting of cathepsin S represents a novel method of inhibiting angiogenesis. Furthermore, when used in combination with anti-VEGF therapies, Fsn0503 has the potential to significantly enhance current treatments of tumour neovascularisation and may also be of use in the treatment of other conditions associated with inappropriate angiogenesis.